Effectiveness of Plant Bioactive Compounds as Colorectal Cancer Cell Line Inhibitors: A Systematic Review - Fadillah; Aulia Rahmi; Aldi Tamara Rahman; Nurul Annisa; Muhammad Hamdi Ibrahim; Rihadatul Aisyah; Reziq Marchellino Irwan; Rita Maliza (Jurnal Biologi Tropis, 2023)
Cancer is a non-communicable disease and one of the highest causes of human death. It has been well documented that active substances have been shown in vitro to have anticancer properties. The purpose of this article is to examine the therapeutic implications of active substances involved in colorectal anticancer activity. We looked through the databases of PubMed, Science Direct, and Google Scholar in our systematic review to find papers released between 2013 and 2023. Ten studies were selected and published between 2013 and 2023. From the results obtained on plant data used as colorectal anticancer, it was reported that plants contain active phenolic compounds, flavonoids, alkaloids, gallic acid, saponins, triterpenoid/steroid, hydroquinones, triterpenoids, phenols, glycosides, quercetin, kaempferol, artemisinin, and tannins that can act as colorectal anticancer agents and are proven to be an inhibitor of cell line growth in colorectal cancer.